Strategi Pemasaran Konten Kreatif Dan Keterlibatannya Dalam Membangun Kesadaran Brand Halal Pada Audiens Di Eropa - Suri, Sabrina Kharisma; Adinugraha, Hendri Hermawan (UNIB Press, 2025)
Advances in digital technology have revolutionized halal product marketing strategies at the global level, particularly through the use of social media and creative content. This article aims to evaluate the role of creative content marketing strategies in building halal brand awareness among digital audiences in Europe. The method used is qualitative descriptive with a literature study approach from journals, articles, books, and related reports. The results of the study show that creative content-based marketing strategies, such as storytelling, interactive campaigns, and collaborations with influencers, can increase emotional engagement and brand awareness on social media platforms. Furthermore, content marketing is considered more effective than conventional strategies in attracting attention and building long-term relationships with consumers, both Muslim and non-Muslim. These findings emphasize the importance of digital content innovation in expanding halal market penetration in Western regions with diverse social and cultural characteristics. It is recommended that halal industry players further integrate creative approaches and continuous evaluation to enhance the impact of their marketing strategies.